Didactic sequences from the perspective of teaching-learning theories - de Sousa Silva, Lilianne (2025)
Science teaching encourages the development of scientifically literate students, i.e. students who know how to use the scientific knowledge learned in the classroom to make sound decisions in everyday life. This influences researchers to seek a break with “traditional” methodologies and promote the use of tools/methodologies that can help develop scientific literacy, such as Didactic Sequences. Through a systemic analysis of the literature, this article aims to understand how the theories of teaching and learning defended by Jean Piaget, Lev Vygotsky and Paulo Freire are references in the construction of Didactic Sequences aimed at promoting Scientific Literacy. The data collected shows that the Didactic Sequence is based on the theories of Piaget, Vygotsky and Freire.